Nature & Spirit: A Digital Lens of Gay-Male Culture. - Gellis, Brandon S. (Reconstruction: Studies in Contemporary Culture, 2016)
The article examines the way by which culture has suppressed gay-male behaviours and fueled the formation of support networks and popular gay characteristics.